1996
DOI: 10.1002/(sici)1096-9861(19960304)366:2<207::aid-cne2>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Organization in the somatosensory sector of the cat's thalamic reticular nucleus

Abstract: This study describes the organization of cells in the thalamic reticular nucleus (TRN) that project to the somatosensory part of the dorsal thalamus in the cat. Injections of wheat germ agglutinin conjugated to horseradish peroxidase (WGA-HRP) and fluorescent dyes were made into the ventrobasal complex (VB) and the medial division of the posterior complex (POm) of the thalamus. The resultant retrograde labelling in TRN was analyzed. Large injections of a tracer in VB label many reticular cells that are restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 88 publications
2
34
0
Order By: Relevance
“…Notice that the RTN is abundantly innervated by cholinergic fibers that may contribute to modulate the firing properties of its neurons in vivo (Jones 1991;Villa et al 1996). Spatial organization of the rostral and somatotopic sector of RTN was observed on the basis of its connectivity pattern and sensory-evoked activity in several species, namely in the rat (Shosaku et al 1984;LozsĂĄdi 1994;Pinault et al 1995), rabbit (Crabtree 1992), and cat (Crabtree 1996).…”
Section: Four Firing Types Characterize the Mouse Rtnmentioning
confidence: 99%
“…Notice that the RTN is abundantly innervated by cholinergic fibers that may contribute to modulate the firing properties of its neurons in vivo (Jones 1991;Villa et al 1996). Spatial organization of the rostral and somatotopic sector of RTN was observed on the basis of its connectivity pattern and sensory-evoked activity in several species, namely in the rat (Shosaku et al 1984;LozsĂĄdi 1994;Pinault et al 1995), rabbit (Crabtree 1992), and cat (Crabtree 1996).…”
Section: Four Firing Types Characterize the Mouse Rtnmentioning
confidence: 99%
“…5 A, B) and mostly restricted to the same mediolateral portion of nRt containing the soma. nRt is topographically organized along the mediolateral axis with three divisions (lateral, central, and medial tiers), each interconnected with a specific thalamic relay nucleus (Crabtree, 1996). This suggests that intra-nRt connections primarily mediate communication within functionally related tiers of nRt.…”
Section: Mapping Of the Synaptic Connectivity Within Nrtmentioning
confidence: 99%
“…Topographic and sensory modality-specific organization exist in nRt both longitudinally (sectors), as well as within the mediolateral extent of the nucleus (tiers) (Jones, 1975;Shosaku et al, 1984;Crabtree, 1996;Crabtree et al, 1998;Lam and Sherman, 2005). For example, neurons located in the central tier of somatosensory nRt project to the ventral posterior nuclei, whereas medial tier neurons connect to the posterior complex (Crabtree, 1996). Thus, our results showing that synaptic connectivity is restricted to neurons located in the same nRt tier suggest that nRt cell interactions occur primarily between cells projecting to the same relay nucleus.…”
mentioning
confidence: 99%
“…First, in agreement with our experience in rats , the reticulothalamic input to the ventral posterior nucleus is already highly topographic even at this age, suggesting an early development of the somatosensory system in rats and mice. Second, injection of retrograde tracers into the posterior nucleus has indicated that differences between the reticular inputs to the first-and higher-order relays are found in adults (Crabtree 1996;Crabtree et al 1998).…”
Section: Technical Considerationsmentioning
confidence: 99%
“…One difference is suggested by prior retrograde tracing studies in cats and rats: the higher-order posterior nucleus was reported to have a more diffusely organized reticulothalamic input compared with the first-order ventral posterior nucleus (Crabtree 1996;Crabtree et al 1998). Labeling of a large number (ÏŸ100) of cells juxtacellularly in the somatosensory and other sections of the thalamic reticular nucleus of rats, however, has led to a somewhat different conclusion, namely, that the axonal arbors of reticular neurons are mostly circumscribed, quite topographically organized and usually contained within a single thalamic nucleus (Pinault and DeschĂȘnes 1998;Pinault et al 1995).…”
Section: Introductionmentioning
confidence: 97%